ROLE OF WATER IN THE SYNTHESIS OF FLY ASH BASED GEOPOLYMER AND THE EFFECT ON UREA DIFFUSION THROUGH THIN FILM - ASIF, AFSHAN (2015)
Urea is commonly used as a fertilizer. Its demand and usage is increasing day by day. The primary issues associated with urea is, within 2 to 4 days of application, nitrogen is released in the form of ammonia which cause environmental pollution and frequent/multiple application increase the cost of fertilizer. According to the basic approach of the controlled release fertilizer (CRF) technology, it should overcome all the problems which is produced by urea. To some extent CRF is able to resolve the problems such as minimize the huge applications of urea. However, it elevates some of the existing issues for instance high cost, nonbiodegradibility which cause environmental pollution. Geopolymer is being used for the variety of applications, which is driven by its good properties such as, high compressive strength, controllable setting time and low permeability.